LANDASAN HUKUM TERHADAP PERILAKU MAIN HAKIM SENDIRI DALAM PERSPEKTIF SOSIOLOGI HUKUM - Muhammad Riefky Alfathan; Riky Praasetia; Sailan Holilul Azfa; Rosyad Syahidin; Pratama Zulkarnaen; Beni Ahmad Saebani (Jurnal Hukum Lex Generalis, 2024)
This article examines the relationship between societal development and law in the context of social change influenced by globalization and technological progress. Using classical theories such as Auguste Comte's "Law of Three Stages" and Karl Marx's historical materialism, as well as the legal positivism approach of Jeremy Bentham and Hans Kelsen, this article analyzes how law adapts to contemporary social challenges. Case studies in Indonesia, mass violence in Pati and Bekasi and violence against children in Tangerang. This research uses a normative juridical approach with literature study techniques and qualitative analysis to provide an understanding of the role of law in dealing with social change. The research results show that mass violence, which is often driven by distrust of the formal legal system, can be explained through Durkheim's theory of solidarity and anomie, as well as Marx's perspective on inequality.